Conductivity Studies of Binary Mixtures of Ionic and Non-ionic Surfactants at different Temperatures and Concentrations. - GB Cookey; FB Nwokobia (Journal of Applied Sciences and Environmental Management, 2014)
Conductivity studies of aqueous solutions of binary mixtures of sodium dodecyl sulphate (SDS), an ionic surfactant and n-decyl-n,n-dimethyl-3-ammonio1-propanesulfonate (DPS), a non-ionic surfactant have been carried out at different concentrations and temperatures. The results show that the conductivity of the solutions of SDS increased with increasing temperature but decreased as the concentration of DPS increased. It was also observed that the concentration at which SDS aggregates or micelles begin to form in solution, called critical micelle concentration (CMC) extrapolated from inflection points on the conductivity versus concentration curves increased with increasing temperature but decreased as the concentration of DPS increased. These results have been discussed in terms of the influence of the molecular architecture of SDS and DPS headgroups on mixed micelle formation. © JASEM